A Review on Current Land Policy issues in India - Arundhatee Mishra (AG Volumes, 2022)
Both policymakers and academics in India remain concerned about the country's land issues. A recent uptick in attention to land disputes may be traced back to the presumed effects of economic liberalisation and openness. A fresh look is being taken at land tenancy, land use limits, and land management. Legalizing tenancy, updating ceiling limitations, quality of land, and addressing the dilemma of minuscule holdings as a result of marginalisation and land management are among the concerns receiving increasing emphasis. All of these concerns are discussed in the following study. It provides context for the development of land policy in India before to Independence and then traces that policy's evolution through its many stages, outlining the policy's consequences and the difficulties it has spawned. Once the history of land policy over different eras of planning have been examined, the concerns of the 1990s may be examined. In conclusion, the need for a new land-policy framework is argued for, which would include changes to the way land records are kept, how hidden tenancy and unprofitable land holdings are handled, and how the issue of poor land quality is addressed. With the recent shift in rural economies, these concerns have taken front stage.